2021
DOI: 10.21161/mjm.211111
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of lactic acid bacteria from sugarcane waste

Abstract: Aim: Researchers are focusing more on the isolation of new probiotic bacteria to increase varieties for the growing market demand. This study aimed to isolate lactic acid bacteria (LAB) strains from sugarcane waste materials and evaluate its characteristic. Methodology and results: In the present study, two strains of LAB (Isolate A and B) were isolated from sugarcane waste and investigated in vitro for their characteristics as potential probiotics. These isolates were evaluated on their characteristics based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…It's been demonstrated that having brackets and ligatures increases the risk of tooth surface decalcification, which eventually leads to the development of caries and white spots on teeth. It also increases gingival irritation [9,10,39].…”
Section: Development Of Bacterial Biofilms On Self-ligating Versus El...mentioning
confidence: 99%
“…It's been demonstrated that having brackets and ligatures increases the risk of tooth surface decalcification, which eventually leads to the development of caries and white spots on teeth. It also increases gingival irritation [9,10,39].…”
Section: Development Of Bacterial Biofilms On Self-ligating Versus El...mentioning
confidence: 99%